Stabilization of p27Kip1/CDKN1B by UBCH7/UBE2L3 catalyzed ubiquitinylation: a new paradigm in cell‐cycle control. Issue 1 (16th August 2018) - Whitcomb, Elizabeth A.; Tsai, Yien Che; Basappa, Johnvesly; Liu, Ke; le Feuvre, Aurélie K.; Weissman, Allan M.; Taylor, Allen
ABSTRACT: Ubiquitinylation drives many cellular processes by targeting proteins for proteasomal degradation. Ubiquitin conjugation enzymes promote ubiquitinylation and, thus, degradation of protein substrates. Ubiquitinylation is a well‐known posttranslational modification controlling cell‐cycle transitions and levels or/and activation levels of ubiquitin‐conjugating enzymes change during development and cell cycle. Progression through the cell cycle is tightly controlled by CDK inhibitors such as p27 Kip1 . Here we show that, in contrast to promoting its degradation, the ubiquitin‐conjugating enzyme UBCH7/UBE2L3 specifically protects p27 Kip1 from degradation. Overexpression of UBCH7/UBE2L3 stabilizes p27 Kip1 and delays the G1 ‐to‐S transition, while depletion of UBCH7/UBE2L3 increases turnover of p27 Kip1 . Levels of p21 Cip1/Waf1, p57 Kip2, cyclin A and cyclin E, all of which are also involved in regulating the G1 /S transition are not affected by UBCH7/UBE2L3 depletion. The effect of UBCH7/UBE2L3 on p27 Kip1 is not due to alteration of the levels of any of the ubiquitin ligases known to ubiquitinylate p27 Kip1 . Rather, UBCH7/UBE2L3 catalyzes the conjugation of heterotypic ubiquitin chains on p27 Kip1 that are proteolytically incompetent. These data reveal new controls and concepts about the ubiquitin proteasome system in which a ubiquitin‐conjugating enzyme selectively inhibits and may even protect, rather than promote degradation of a crucial cell‐cycle regulatory molecule.—Whitcomb, E. A., Tsai, Y. C., Basappa, J., Liu, K., le Feuvre, A. K., Weissman, A.M., Taylor, A. Stabilization of p27Kip1/CDKN1B by UBCH7/UBE2L3 catalyzed ubiquitinylation: a new paradigm in cell‐cycle control. FASEB J. 33, 1235–1247 (2019). www.fasebj.org